Alpha-Spin-Mediated Growth Factors Improvement for Tomato (Lycopersicon esculentum Mill.) Varieties in Jauro Yinu, Ardo-Kola LGA, Taraba State (Lafia Journal of Scientific and Industrial Research, 2024)
The study was conducted to investigate the improvement achieved through the treatment of two tomato varieties (ANSAL and Dan-Zaria) with Alpha-Spin® nanoparticles in a screenhouse at Jauro Yinu in Ardo-Kola LGA, Taraba State, Nigeria. Seeds were exposed to the Alpha-Spin® nanoparticles® for durations of 15, 30, 45, and 60 minutes before planting, using a Randomized Complete Block Design with a control group. The results of data collected and analyzed using GENSTAT statistical software showed that Alpha-Spin® treatments did not affect germination time (which was 7 days after planting for ANSAL and 3 days for Dan-Zaria in all exposures) or plant height (Dan-Zaria: 148.33 cm). However, it significantly improved other growth parameters, including stem girth (Dan-Zaria: 19.33 mm), number of branches (Dan-Zaria: 11), flowering time (27 days after transplanting for Dan-Zaria and 31 days for ANSAL with 15 minutes exposure), and number of flower clusters (ANSAL: 37). Overall, Dan-Zaria exhibited better growth than ANSAL in most of the growth parameters. These results indicate that exposure to Alphaspin® nanoparticles enhanced the growth parameters like stem girth, number of branches per plant, and days to 50% growth) in tomato varieties, making it a recommended treatment for trait improvement in tomato breeding programs.
Keywords: Alpha-Spin; Growth; Improvement; Taraba; Tomato